Perancangan Prototype Sistem Pendaftaran Pasien Berbasis Android di Rumah Sakit Bhayangkara Batam - Nurwana, Mulia; Anisa, Desfa; Farhansyah, Fani (Penerbit Goodwood, 2022)
Purpose: The purpose of this research is to design a prototype Android-based patient registration system at the Bhayangkara Batam Hospital. Research methodology: The research method used in this research uses descriptive qualitative research methods, with data collection techniques of interviews, observations, literature studies and experiments. For system design in this research, researchers used the prototype method to design the system. Results: From this research, an Android-based patient registration system prototype was designed which can assist officers in registering patients. Patients can register independently and do not need to wait to be registered by an officer. From the designed prototype, two prototype designs were made, namely the admin prototype and the patient prototype. Limitations: This research only focuses on designing a prototype of an Android-based patient registration system. Contribution: Designing a prototype of an Android-based patient registration system will help officers register patients and provide information to patients so that patients know the queue number to the designated polyclinic.